Persepsi Siswa Terhadap Pelaksanaan Perpustakaan Di SMA Negeri 12 Pekanbaru - Ajir (Jurnal Gema Pustakawan, 2013)
Libraries have common functions and tasks are as collectors, processors and disseminators of information to use library, because the school library serves as supporting elements, is essentially a unit of work that is an integral part of their parent institutions which together another unit, but in different roles, assigned to assist the school in question in the learning task. The school library will not be meaningful for teaching and learning, where students and other visitors have a poor perception of the existence of the library. The purpose of this study was to determine the students' perceptions of the implementation of the library in high school (SMA) State 12 Pekanbaru. The method used is descriptive research where research is conducted on an independent variable, that is, without making comparisons or connect with other variables. Based on the results of research on the implementation and management officers known library ranging from procurement of materials to the work of collection of administrative services at SMAN 12 Pekanbaru included in the medium category.